Moderating Role of Effective Counselor Characteristics in the Relationship between the Behaviors of Counselors' Supervisors and their Professional Pride and Job Satisfaction - Yildirim Kurtulus, Hacer; Yuksel Sahin, Fulya (HACETTEPE UNIV, 2023)
This study explored the moderating role of effective counselor characteristics in the relationship between the behaviors of counselors' supervisors and the professional pride and job satisfaction of counselors. The study group consisted of 661 counselors. The researchers used the Supervision Questionnaire, Effective Personal Information Form to collect the study data and Regression-Based Bootstrapping Technique for data analysis. The research results demonstrated a significantly positive relationship between counselors' professional pride and job satisfaction on one hand and their effective counselor characteristics and supervisors' behaviors on the other. The researchers found that the behaviors of counselors' supervisors directly, positively, and significantly predicted their effective counselor characteristics. They also found that effective counselor characteristics directly, positively, and significantly predicted counselors' professional pride and job satisfaction. Another finding was that effective counselor characteristics played a partial moderating role in the relationship between the behaviors of counselors' supervisors and their professional pride. The results suggested that counselors' job satisfaction is directly, positively, and significantly predicted by effective counselor characteristics. Effective counselor characteristics also played a partial moderating role in the relationship between the behaviors of counselors' supervisors and their job satisfaction. The research results were discussed in the light of literature.
Keywords: Supervision; supervisor behaviors; effective counselor characteristics; professional pride; job satisfaction; SELF-EFFICACY; CLINICAL SUPERVISION; WORKING ALLIANCE; MEDIATOR; STUDENTS; OUTCOMES; SUPPORT; Education & Educational Research